The ‘Rainbow Nation’ way of teaching sensitivity to diversity for social work with groups - Prinsloo, Reineth (Groupwork, 2012)
Because social work clients are often members of oppressed, vulnerable and disempowered groups, teaching sensitivity to diversity and empowering social work students to be culturally competent is of the utmost importance. South Africa’s history of apartheid has had detrimental effects on personal, social, economic, and political development. A department of social work at a university in South Africa introduced specific study units within its Bachelor of Social Work (BSW) programme to address the influence of this particularly vicious form of discrimination. The units help students to confront their own prejudices, enhance their self-awareness, and obtain knowledge of and exposure to diverse client populations. This paper discusses the need for coursework in this area, and describes the process of teaching these study units.